Noncognitive skills, occupational attainment, and relative wages. - Cobb-Clark, Deborah; Tan, Michelle (My University, 2009)
This paper examines whether men's and women's noncognitive skills influence their occupational attainment and, if so, whether this contributes to the disparity in their relative wages. We find that noncognitive skills have a substantial effect on the probability of employment in many, though not all, occupations in ways that differ by gender. Consequently, men and women with similar noncognitive skills enter occupations at very different rates. Women, however, have lower wages on average not because they work in different occupations than men do, but rather because they earn less than their male colleagues employed in the same occupation. On balance, women's noncognitive skills give them a slight wage advantage. Finally, we find that accounting for the endogeneity of occupational attainment more than halves the proportion of the overall gender wage gap that is unexplained.
IZA Discussion Papers
Keywords: Employment -- Occupations and careers; Gender -- Gender differences; Beliefs and Values -- Personality; Income & Finance -- Wage gap; Gender; Income, wealth and finances; Labour market; Gender; Employment; Beliefs and Values; Income & Finance; Wage gap; Gender differences; Personality; Occupations and careers; Gender; Employment and unemployment; Income, wealth and finances